Kebiasaan Menggosok Gigi Sebelum Tidur Terhadap Riwayat Karies Pada Anak - Abubakar, Syamsuddin; AR, Sainuddin; Jayanti, Nur Fitri (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Dental caries is a dental and oral disease that is often found in children and adults. In maintaining dental health, the most common thing to do is brush your teeth properly and correctly. The aim of this research is to determine the relationship between the habit of brushing teeth before bed and the history of caries in elementary school children. This research uses a cross sectional approach. namely by looking for relationships between variables within a certain time frame. The sample in this study was 41 students at SD Negeri 257 Akkalibate District. Liliriaja District. Soppeng. In this research, dental examinations will be carried out on the samples. data analysis using the Pearson Colleration. The results of this research show that the majority of respondents are children of SD Negeri 257 Akkalibatue Kec. Liliriaja, Soppeng Regency, experienced dental caries. The correlation test obtained a sig value. (2-tailed) 0.05, namely 0.580, which means there is no significant correlation. Based on this, Ho is rejected and Ha is accepted, which states that there is no relationship between the habit of brushing teeth and dental caries. Statistical analysis shows that the habit of brushing teeth before bed does not have a significant influence on the incidence of dental caries in elementary school children. It is necessary to provide intensive education about the importance of the habit of brushing teeth before bed among children, parents and the general public in the area.